Peer Influence and Single Parenting as Predictors of Sexual Abuse Among Secondary School Students in Nigeria - Martins, Igbineweka Noyosase; Omogbai, Edith Omorionmwen (Universitas Mercu Buana Yogyakarta, 2024)
This study examined peer influence and single parenting as predictors of sexual abuse among secondary school students in Ovia North East Local Government Area of Edo State, Nigeria. Two research questions were raised and two hypotheses were formulated. The correlational survey research design was used for the study. The population of the study is Eleven thousand nine hundred and eighty-five (11985) senior secondary school students in the public and private schools in Ovia North East Local Government Area. The multistage sampling procedure was employed to select 300 students from six (6) senior secondary schools in Ovia North East Local Government Area. The research instrument was a questionnaire titled